1997
DOI: 10.1038/ng0397-307
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous ATM mutations do not contribute to early onset of breast cancer

Abstract: Ataxia telangiectasia (AT) is a recessive syndrome, including cerebellar degeneration, immunologic defects and cancer predisposition, attributed to mutations in the recently isolated ATM (ataxia telangiectasia, mutated) gene. AT is diagnosed in 1/40,000 to 1/100,000 live births, with carriers calculated to comprise approximately 1% of the population. Studies of AT families have suggested that female relatives presumed to be carriers have a 5 to 8-fold increased risk for developing breast cancer, raising the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
151
2
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(166 citation statements)
references
References 32 publications
12
151
2
1
Order By: Relevance
“…However, this association has been subject to some controversy. A study of young patients with breast cancer (and no known family history of A-T syndrome) detected heterozygous truncating ATM mutations in only 0.5% of cases, less than the rate predicted by the preceding studies, and even less than the general population, suggesting that such heterozygous ATM mutations did not predispose those individuals to breast cancer (26). The slightly different patient characteristics may account for the discrepant results between these studies.…”
Section: Germ-line Atm Heterozygosity and Cancer Susceptibilitycontrasting
confidence: 38%
“…However, this association has been subject to some controversy. A study of young patients with breast cancer (and no known family history of A-T syndrome) detected heterozygous truncating ATM mutations in only 0.5% of cases, less than the rate predicted by the preceding studies, and even less than the general population, suggesting that such heterozygous ATM mutations did not predispose those individuals to breast cancer (26). The slightly different patient characteristics may account for the discrepant results between these studies.…”
Section: Germ-line Atm Heterozygosity and Cancer Susceptibilitycontrasting
confidence: 38%
“…From this they were able to derive an estimated odds ratio (OR) of 3.8 (95% CI 1.7Ð8.4) for the risk of breast cancer in heterozygotes. In contrast, however, Fitzgerald et al (1997) found no increased risk of breast cancer in young heterozygote women. They performed a germ-line mutational analysis of 401 women with breast cancer diagnosed at under age 40 and compared them with similar analyses of 202 controls.…”
Section: Discussionmentioning
confidence: 65%
“…These findings are consistent with two earlier studies: one study of the British families that first identified the 7271T4G mutation and reported a similarly large increased risk of breast cancer among three carriers of that mutation (RR ¼ 12.7, 95% CI 3.7 -45.8) (Stankovic et al, 1998); and a second study by Broeks (Broeks et al, 2000) of earlyonset female breast cancer, where three out of the seven ATM mutations found were IVS10-6T4G. While not all studies of ATM gene mutations demonstrate an excess risk of breast cancer (FitzGerald et al, 1997;Bebb et al, 1999;Shafman et al, 2000), studies that have screened for missense mutations (Athma et al, 1996;Teraoka et al, 2001) and those that have examined risk among family members of A-T patients (obligate heterozygotes) (Swift et al, 1987(Swift et al, , 1991Pippard et al, 1988;Borresen et al, 1990;Inskip et al, 1999;Olsen et al, 2001) have consistently found an elevated risk. Combined, these results provide evidence for an increased breast cancer risk associated with specific ATM gene mutations.…”
mentioning
confidence: 98%